Proposed development of Eco-Park at Universiti Putra Malaysia (UPM) - Mohammed, Safwan Rosidy; Vijayasree, Vijaya Prakash; Che Rozali, Norhanan Syahirah; Shai-in, Mohammad Fitri; Ku Ayob, Ku Adriani; Ismail, Nooredlin; A.A., Fatiah; Ponrahono, Zakiah (IIUM Press, 2020)
The following project paper puts forward a proposal for an Eco-Park in Universiti Putra Malaysia (UPM), a higher educational institute located in the state of Selangor in Malaysia. The proposed site has a strategic location because of its proximity to the highway, a commuting line and is situated near to a major city (i.e. Kuala Lumpur). The natural features present are namely a lake, a stretch of river and a secondary forest. The potential social benefit from the development of the Eco-Park is that it can serve as a recreational space that is easily accessible by residents, students and the general public. Meanwhile, the environmental benefits of the Eco-Park are that it will serve as a governed space for the preservation of the natural features (i.e. vegetation and water bodies), which will potentially improve the ecosystem services in the proposed location. An added benefit of the park is that it can promote a scenic view for the public commuting through the area. Presently, a Metro Transit Line (MRT) is in construction next to the proposed site; thus, source of funding can be channelled by the MRT developer as a means to strike a balance for clearing of the area.